Analisis perbandingan kinerja portofolio saham LQ 45 dengan kinerja portofolio saham JII (Jakarta Islamic Index) periode Januari 2007-November 2009 - ABIDIN, Rakhmad ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Capital market has become a medium for a company to get the fund for its persistence. And this capital market is also used by investors to utilize their capital to obtain profit from dividend as well as capital gain. In this time, investors given on to many choices of investment or portfolio residing in capital market, so that they have to knowing how return and risk according to expense and time which they sacrifice. Therefore this research aimed to analyze the comparison of performance of portfolio share as an instrument of investment in capital market. As for comparison object, the portfolio of LQ 45 and portfolio of Jakarta Islamic Index (JII) were selected at the period of January 2007 till November 2009. This research used the historical data in the form of daily return share, market return which in this case was market portfolio (IHSG) and monthly rate of interest of Indonesia Bank Certificate (SBI). The data were processed to monthly data using the geometric mean. The portfolio formed by simple random sampling consisted of 3 share, 5 share and 10 share. For the assessment of portfolio performance, this research used Sharpe, Treynor and Jensen method. The result indicated that the z-test between portfolio of LQ 45, portfolio of JII as well as market portfolio were not significant at 5% level of confidence, but the value of parameter Sharpe, Treynor and Jensen, assessed for the portfolio of share LQ 45 and JII, still resided in above value of market portfolio (IHSG). Thereby, though Islamic capital market in this time was emerging, but there was no evidence to say that the performance of Islamic portfolio was better than the LQ 45 portfolio or market portfolio.